Prevalence, Antimicrobial Resistance, and Molecular Description of Pseudomonas aeruginosa Isolated from Meat and Meat Products. (13th October 2022) - Rezaloo, Manizhe; Motalebi, Abbasali; Mashak, Zohreh; Anvar, Amirali
Abstract : Resistant and virulent Pseudomonas aeruginosa ( P. aeruginosa ) bacteria are measured as the major cause of food spoilage and food-borne diseases. This survey assesses the prevalence, antibiotic resistance properties, and virulence factors distribution in P. aeruginosa bacteria isolated from meat and meat products. A total of 370 raw, frozen, and imported bovine meat samples and diverse types of meat product samples were collected from Alborz province, Iran. P. aeruginosa bacteria were identified by culture. Disk diffusion was used to assess the antibiotic resistance of bacteria. Furthermore, the PCR was used to assess the virulence and antibiotic resistance genes. Twenty nine out of 370 (7.83%) samples were contaminated with P. aeruginosa . Imported frozen bovine meat (20%) harbored the highest distribution, while sausage (2%) harbored the lowest. High resistance rates were observed toward ampicillin (89.65%), penicillin (86.20%), tetracycline (82.75%), cefoxitin (37.93%), gentamicin (34.48%), and clindamycin (31.03%). The most commonly detected antibiotic resistance genes were bla DHA (93.10%), bla CTX-M (83.65%), and bla SHV (48.27%). Bla DHA (93.10%), bla CTX-M (83.65%), and bla SHV (48.27%) were the most frequently detected resistance genes. The most commonly detected virulence genes were exoS (75.86%), lasA (68.96%), exoU (58.62%), lasB (51.72%), plcH (48.27%), and algD (44.82%). Meat and meat product samples may be sources of P. aeruginosa, which show an important threat to their consumption. Nevertheless, additional inquiries are obligatory to find supplementary epidemiological properties of P. aeruginosa in meat and meat product samples.